Towards common terminology on energy landscapes - preface - Marot, Naja; Kruse, Alexandra (JOURNAL OF LANDSCAPE ECOLOGY, 2018)
The COST RELY Glossary on Renewable Energy and Landscape Quality is the result of the European COST RELY project that focused on investigating the influence of renewable energy production on landscape quality. 31 people participated in developing and revising the definitions and descriptions for the 46 terms included in the glossary. Work was done in the period from 2015 to 2017 in multiple rounds of revision done by the RELY experts. Terms in the glossary are clustered into three groups: first group terms are directly connected to the landscape and its characteristics, the second one touches the planning process and methods, and the last one covers different renewable energy sources and production types. Each entry to the glossary consists of six elements: the term, definition, related terms, keywords, illustration(s) and sources. The terms are based on the expert knowledge of the contributors, scientific literature (monographs and articles), EU regulation, relevant web pages and other useful sources, stated in the Reference section. At the end of the glossary, terms are translated into 28 European languages including Esperanto. The glossary targets the researchers from the field, policy makers, local communities, investors in the sector of renewable energy and NGOs concerned with the matter in order to assure that people from different educational background and profession understand and use the term in the same manner. Beside from internal Action use, the terms shall contribute to existing glossaries on the relevant topics.